Assessing use of power point by teacher candidates in teaching mathematics - M Aminah; E T Wahyuni (International Conference on Mathematics and Science Education of Universitas Pendidikan Indonesia, 2018)
The use of PowerPoint technology in the classroom has become very popular today because it is considered to enhance teaching quality. However, its use is not free from criticism with the emergence of phrases such as 'PowerPoint is Evil' and 'Death by PowerPoint'. Mathematics and teaching-learning mathematics have certain characteristics. Hence, the creation and execution of presentation in the class with PowerPoint format requires certain handling as well. This study intends to explore students' perceptions and teachers' judgments on the use of PowerPoint in mathematics teaching by teacher candidates. Participants in this study were 14 math teacher candidates, 5 math teachers, and 421 students of two vocational high schools. The student questionnaire result shows that with PowerPoint presentations, in general, students are motivated and helped to learn math, value the management of slide shows quite well, but tend to only listen to the teacher during the learning process, and feel that sometimes lessons are easier with PowerPoint, sometimes not. Teachers' observation result shows that most of the teacher candidates are good enough in organizing subject matter and slides of presentations.